Exploring the mental model of cattle farmers in disease prevention and control practices - Yong, Suit B.; Hassan, Latiffah; Krauss, Steven Eric; Ramanoon, Siti Zubaidah; Ooi, Peck Toung; Abd. Rahaman, Nor Yasmin; Epstein, Jonathan H. (MDPI, 2020)
Farmers play an integral role in minimizing disease threats and managing ongoing diseases on their farms. Various environmental factors influence the decision-making processes of farmers. Deciphering the mental models of farmers allows us to understand the motivations and reasons behind disease prevention and control choices. This study aimed to explore the mental models of cattle farmers in implementing disease prevention and control practices. Using qualitative in-depth, semi-structured interviews, seven cattle farmers from a university’s foster farm extension program were sampled. Interview transcripts were analyzed using inductive content analysis. Results revealed 23 dimensions comprising the mental model of cattle farmers. The dimensions were conceptualized under four major themes. Farmers were most influenced by perceived risk of disease, perceived effectiveness and benefits of disease prevention and control practices, experience, knowledge and emotions, subjective norms and perceived economic loss. The decision-making processes of farmers are complex and are influenced by various factors. While additional research is needed to confirm the findings using quantitative methods and larger sample sizes, insights gained from the study can be used as inputs to tailor communication and training strategies for improved disease prevention and control interventions.